Calidad de vida en pacientes con tuberculosis pulmonar relacionado con el Autoestima, Centro de Salud Cono Sur. julio - setiembre 2018 - Enriquez Choquehuanca, Katherin Betza (2019)
Objective: To describe the quality of life related to self-esteem in patients with pulmonary tuberculosis of the Southern Cone Health Center of the city of Juliaca, July to September 2018 Material and methods: it is a non-experimental design research of an analytical, descriptive, cross-sectional type with a sample of 40 patients with pulmonary tuberculosis. Results: The quality of life related to self-esteem in patients with pulmonary tuberculosis of the Southern Cone Health Center of the city of Juliaca, during the period from July to September 2018, are: the age 67.50% are from 21 to 35 years, 60% are male, 40% secondary education, 35% live together, systematic diseases 10% have high blood pressure, 47.50% do not perform physical activities, 25% are housewives, 45% live in rented house, 67.50% use public transport, 50% there are some problems, 40% have no friends, 20% just once felt happy, 42.50% almost always feel discouraged and sad, 47.50% almost always they feel exhausted or tired, emotional problems have hindered their social activities of the patient 47.50% almost always, all with a level of significance P <0.05, Conclusion: Self-esteem in patients with pulmonary tuberculosis, 47.50% self-esteem low, 30% medium self-esteem, 22.50% high self-esteem.